Vegetation Structure and Composition in the Coban Talun Pine Forest, Batu City, East Java, Indonesia: A Plot-Based Analysis - Anggun Wulandari; Fatikhatun Nikmatus Sholihah; Rossanita Truelovin Hadi Putri; Moch Faizul Huda (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
This study aims to analyze the vegetation structure and composition of the Coban Talun Pine Forest in Batu City, East Java, Indonesia, using a plot-based approach. A quantitative descriptive method was applied through field surveys conducted in six sampling plots measuring 1.5 m × 1.5 m. A total of 24 plant species were identified, consisting of herbs, grasses, shrubs, ferns, bryophytes, and limited tree regeneration. The vegetation was dominated by understory species, particularly Paspalum conjugatum, Colocasia esculenta, and Marsilea crenata. Vegetation structure was analyzed using ecological parameters including density, frequency, and dominance, which were further integrated into the Important Value Index (IVI). The results showed that Paspalum conjugatum had the highest IVI value, indicating its strong ecological dominance and adaptability. Overall, the vegetation structure was uneven, with dominance concentrated in a few species, reflecting a moderately diverse but disturbance-influenced ecosystem. Environmental factors such as altitude, temperature, and light availability contributed to the observed vegetation patterns. The findings provide baseline ecological data that can support biodiversity conservation and sustainable forest management in the Coban Talun area.